Occupations, Human Capital and Skills. - Levenson, Alec; Zoghi, Cindy (Journal of Labor Research, 2010)
Economists have long recognized that occupations can be used as proxies for skills in wage regressions. Yet the potential existence of non-market factors such as discrimination and occupational choice (sorting) on the basis of job attributes that are separate from, but potentially correlated with, wages makes occupations an imperfect control for skills. In this paper, we consider whether inter-occupational wage differentials that are unexplained by measured human capital are indeed due to differences in unmeasured skill. Using the National Compensation Survey, a large, nationally-representative dataset on jobs and ten different components of job requirements, we compare the effects on residual wage variation of including occupation indicators and these skill requirements measures. We find that although these skill requirements vary across 3-digit occupations, occupation indicators decrease wage residuals by far more than can be explained by skill alone. This indicates that “controlling for occupation” does not equate to controlling for only these skill measures, but also for other factors. Additionally, we find that there is considerable within-occupation variation in skill requirements, and that the amount of variation is not constant across skill levels. As a result, including occupation indicators in a wage model introduces heteroskedasticity that must be accounted for. We suggest that caution be applied when using and interpreting occupation indicators as controls in wage regressions. Reprinted by permission of the publisher.